Challenges and Opportunities of Adopting Green HRM in SMEs: Perspectives from Makassar - Haeruddin, M. Ikhwan Maulana (Malaqbi Publisher, 2025)
This study explores the challenges and opportunities of adopting Green Human Resource Management (GHRM) within Small and Medium-sized Enterprises (SMEs) in Makassar, Indonesia. Drawing on in-depth interviews with 28 stakeholders across various sectors, the research reveals significant constraints, including limited financial resources, lack of HR specialization, and low awareness of GHRM practices. A perceived disconnect between environmental initiatives and immediate business benefits compounds these limitations. However, the study also uncovers context-specific opportunities rooted in local cultural values such as siri’ na pacce (honor and compassion) and kearifan lokal (local wisdom), which may serve as effective entry points for GHRM adoption. The findings suggest that incremental, culturally grounded approaches, supported by community networks and localized tools, are more viable than top-down models. This research provides practical insights for policymakers, business owners, and scholars seeking to promote sustainable human resource management (HRM) practices in developing regional economies.